Masterplan Teknologi Informasi dan Komunikasi (TIK) Kantor Pemerintah Desa - Asyikin, Arifin Noor; Fitri, Rahimi; Nugroho, Agus Setiyo Budi (POROS TEKNIK, 2016)
The village is the smallest part of the system of administrative governance in Indonesia,which is required to keep abreast of technological developments and improve its ability tomanage the administrative data the village population. Currently several villages in southernKalimantan, there are many uses conventional technologies in system administrationservices village population. It is very possible impact to village officials and villagers, wherefrequent human error, as well as a waste of time and cost. Therefore, it needs a system thatleads to e-Government to address any problems that occur.In the implementation of e-Government, the Government needed some kind of strategicplanning that is often referred to as the Master Plan for ICT as a base village government inimplementing Information Technology and communication. Preparation of Master Plan ICTto the village administration office is expected to be a guide or reference for the villagegovernment in determining policies, strategic plans, work programs of ICT, ICT developmentunit manager, user management, network infrastructure development, ICT infrastructure,and information systems management guidelinesThe preparation of the ICT master plan begins with identifying the current condition ofthe village so that it can be seen readiness of the village at the time of the master plan willbe applied, and then determine a strategic plan in ICT include information technologyinfrastructure, and management ICT